2023
DOI: 10.1126/scirobotics.adc9800
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying stiffness and forces of tumor colonies and embryos using a magnetic microrobot

Abstract: Stiffness and forces are two fundamental quantities essential to living cells and tissues. However, it has been a challenge to quantify both 3D traction forces and stiffness (or modulus) using the same probe in vivo. Here, we describe an approach that overcomes this challenge by creating a magnetic microrobot probe with controllable functionality. Biocompatible ferromagnetic cobalt-platinum microcrosses were fabricated, and each microcross (about 30 micrometers) was trapped inside an arginine–glycine–apartic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Yet others have shown that living cells can internalize microstructures, such as radio frequency identification (RFID), 12 force and pressure sensors, 13,14 barcodes, 15 magnetic antennas, 16 and microrobots. 17 These studies demonstrate the possibility of interfacing various materials with live cells and tissues. However, a lithographybased technique for systematically integrating nanomaterials onto live cells with a high spatial resolution and yield has yet to be realized.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Yet others have shown that living cells can internalize microstructures, such as radio frequency identification (RFID), 12 force and pressure sensors, 13,14 barcodes, 15 magnetic antennas, 16 and microrobots. 17 These studies demonstrate the possibility of interfacing various materials with live cells and tissues. However, a lithographybased technique for systematically integrating nanomaterials onto live cells with a high spatial resolution and yield has yet to be realized.…”
mentioning
confidence: 84%
“…To address this challenge, researchers have explored alternative approaches to creating biological interfaces, such as depositing force-mediating nanoparticles on cells or 3D bioprinting composite formulations of nanomaterials and cells. However, these biocompatible techniques often possess limited throughput and resolution, especially at submicrometer length scales. Yet others have shown that living cells can internalize microstructures, such as radio frequency identification (RFID), force and pressure sensors, , barcodes, magnetic antennas, and microrobots . These studies demonstrate the possibility of interfacing various materials with live cells and tissues.…”
mentioning
confidence: 94%
“…[185][186][187][188] In one seminal study, a hydrogel microsphere-based magnetic microrobot was designed to quantify both forces and stiffness of tumor colonies. 189 Although these hydrogel-based microspheres are promising, they are difficult to use for characterizing aberrant mechanical properties in tumor tissues in vivo. Nanoparticles are well known for easy modification and versatile functionalities.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Most recent techniques are based on the polymerization of acrylamide, but several studies have utilized other materials, such as alginate or gelatin 24,25 , whose stiffness is harder to control and/or varies within a relatively narrow range, limiting their usability. Polyethylene glycol (PEG) allows for varying stiffness over a wide range and has desirable biocompatibility 26 , although its hydrolytic degradability and autooxidation activity might affect cell function and make it less suitable for applications requiring long-term cell culture. Stable polyacrylamide (PAAm) microspheres with adjustable size and stiffness can be fabricated and made biocompatible by functionalization.…”
Section: Introductionmentioning
confidence: 99%